PERIODS OF MOUTH OPENING AND YOLK ABSORPTION RELATED TO THE ACTIVITY OF DIGESTIVE ENZYMES IN THE EARLY STADIA FROM THE SECOND GENERATION OF HUMPBACK GROUPER BROODSTOCK - Wawan Andriyanto; Muhammad Marzuqi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
The experiment was carried out to determine the exposure time of the first mouth opening on humpback grouper larval from F2 broodstock on hatchery until 10 DAH (days after hatching) because this phase is a critical phase of larval adaptation from food endogenous (from yolk sac) to the ability of absorbing nutrients from external (exogenous). The eggs used were collected from natural spawning of second generation of humpback grouper reared in the tank size of 150 litre. The mouth opening was observed at 90 and 45 degrees under computerize integrated microscope and processed by a specific software. The rate of yolk absorption was observed in larvae from the beginning to the end of breeding, while the activities of digestive enzymes (trypsin and chymotripsin) were analyzed by enzyme assay techniques. The results showed that the period of mouth opening of larvae of humpback grouper occurred at 3 DAH with mouth openings of 45° as large as 0.103 mm and of 90° as large as 0.156 mm. In the early stadia, the diameter of yolk was 0.1875 mm, while the oil globule was 0.0537 mm. At 4 days after hatching, the yolk and oil globule had been absorbed, while the enzymes trypsin and chymotripsin were detected in the early stadia. The results also showed that the larvae was started to use foods from outside after the age of 4 DAH. Up to the age of 10 days, the mouth opening increased and the activity of trypsin and chymotripsin were still detected.Keywords: progeny larvae of humpback grouper F2, mouth opening, yolk sac, enzyme